Pengembangan Platform Berbasis Web untuk Edukasi Gizi dan Deteksi Dini Stunting - Aldhyno Yoghatama; Endang Wahyu Pamungkas (bit-Tech, 2025)
Stunting remains a major public health issue in Indonesia with a prevalence of 21.5%, negatively affecting children’s growth and development. Limited access to interactive and integrated nutrition education poses a barrier to early stunting prevention efforts. This study aims to develop an interactive web-based platform called GiziMu Mijen that integrates evidence-based nutrition education, a nutritional status calculator for children aged 0–60 months based on WHO standards, and an online nutrition consultation service via WhatsApp to support family-level stunting prevention. The system was developed using the Agile Software Development methodology and the Laravel 11 PHP framework, with system design modeled through Unified Modeling Language (UML) for use case, activity, and data structure visualization. Testing was conducted using black-box and acceptance testing involving nutritionists to validate the nutritional calculator and consultation features. Results indicate that the platform successfully provides nutrition education content, complementary feeding recommendations, automated nutritional status calculations, and functional interactive consultation services. The system facilitates parents’ independent monitoring of their children’s nutritional status and quick access to professional advice. In conclusion, GiziMu Mijen offers a comprehensive and effective digital solution to improve nutrition literacy and early stunting detection at the family level. The Agile and Laravel-based development approach ensures flexibility and usability, positioning the platform as a strategic tool in national stunting reduction programs, with recommendations for broader testing and integration into national health information systems for data validation.